Gender-related provisions in regional trade agreements - José-Antonio Monteiro (World Trade Organization (WTO), 2018)
Regional Trade agreements (RTAs) are sometimes viewed as laboratories in which new types of provisions are negotiated to address recent trade-related issues and challenges. A detailed analysis of 556 RTAs, including 292 agreements currently in force and notified to the WTO (as of November 2018), shows that although the inclusion of gender-related provisions in RTAs is not a recent phenomenon, a limited but increasing number of RTAs, namely 74 agreements, refer explicitly to gender-related issues. These gender-related provisions are highly heterogeneous and differ in terms of location in the RTA, language, scope and commitments. Most gender-related provisions are found in a single or couple of RTAs and couched in best endeavour language. In the last three years, a limited number of RTAs have expanded significantly the scope of gender-related provisions by establishing a dedicated article or chapter on trade and gender.
Keywords: F13; F15; 330; Regional Trade Agreements; Gender; Women